Trichotillomania: a case report with clinical and dermatoscopic differential diagnosis with alopecia areata - Ana Cecília Versiani Duarte Pinto; Tatiana Cristina Pedro Cordeiro de Andrade; Fernanda Freitas de Brito; Gardênia Viana da Silva; Maria Lopes Lamenha Lins Cavalcante; Antonio Carlos Ceribelli Martelli (Sociedade Brasileira de Dermatologia, 2017)
ABSTRACT Trichotillomania is a psychodermatologic disorder characterized by uncontrollable urge to pull one's own hair. Differential diagnoses include the most common forms of alopecia such as alopecia areata. It is usually associated with depression and obsessive-compulsive disorder. Trichotillomania treatment standardization is a gap in the medical literature. Recent studies demonstrated the efficacy of N-acetylcysteine (a glutamate modulator) for the treatment of the disease. We report the clinical case of a 12-year-old female patient who received the initial diagnosis of alopecia areata, but presented with clinical and dermoscopic features of trichotillomania. She was treated with the combination of psychotropic drugs and N-acetylcysteine with good clinical response. Due to the chronic and recurring nature of trichotillomania, more studies need to be conducted for the establishment of a formal treatment algorithm.